BANTUAN RUMAH KEPADA KAUM DUAFA OLEH BAITUL MAL KABUPATEN PIDIE DITINJAU MENURUT HUKUM ISLAM (Studi Kasus di Kecamatan Mutiara) - Mariana (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2020)
This study discusses the mechanism of housing assistance for the poor by Baitul Mal in Pidie Regency. The research method used is a descriptive method, in obtaining data in the field the author uses interview techniques, documentation, observation. The results of the study show that the practice of housing assistance for the poor in Mutiara District is provided to the poor by verifying documents from proposals that enter their offices, then conducting surveys and then making appropriate decisions or not. The house of assistance for Dhuafa by Baitul Mal, must have at least 3 children, the house is not livable like the wall has been damaged, the roof has leaked, does not have a master bedroom, the kitchen is unfit for use, thatched roof, the floor of the ground of the like, the house has not been touched help. The review of Islamic law on the practice and mechanism of assistance for aid houses to the poor by Baitul Mal is in accordance with Islamic law because it provides assistance with motivation to wish only Allah's pleasure.